2018
DOI: 10.1186/s40623-018-0862-0
|View full text |Cite
|
Sign up to set email alerts
|

Geospace exploration project ERG

Abstract: The Exploration of energization and Radiation in Geospace (ERG) project explores the acceleration, transport, and loss of relativistic electrons in the radiation belts and the dynamics for geospace storms. This project consists of three research teams for satellite observation, ground-based network observation, and integrated data analysis/simulation. This synergetic approach is essential for obtaining a comprehensive understanding of the relativistic electron generation/loss processes of the radiation belts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
239
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 249 publications
(255 citation statements)
references
References 47 publications
1
239
0
1
Order By: Relevance
“…In this study, we use data from the electric field and waves (EFW) instrument (Wygant et al, ) and search coil sensors for the Electric and Magnetic Field Instrument Suite and Integrated Science (Kletzing et al, ) on board the Van Allen Probe‐A. We also use the waveform data from the wave form capture (WFC) of the Plasma Wave Experiment (Kasahara et al, ; Matsuda et al, ) on board the Arase (ERG) satellite (Miyoshi, Hori, et al, ; Miyoshi, Shinohara, et al, ). The Arase satellite has operated the wave burst observations intermittently to obtain the wave form with the sampling frequency of 1,024 Hz.…”
Section: Analysis Of Van Allen Probe and Arase Observationsmentioning
confidence: 99%
“…In this study, we use data from the electric field and waves (EFW) instrument (Wygant et al, ) and search coil sensors for the Electric and Magnetic Field Instrument Suite and Integrated Science (Kletzing et al, ) on board the Van Allen Probe‐A. We also use the waveform data from the wave form capture (WFC) of the Plasma Wave Experiment (Kasahara et al, ; Matsuda et al, ) on board the Arase (ERG) satellite (Miyoshi, Hori, et al, ; Miyoshi, Shinohara, et al, ). The Arase satellite has operated the wave burst observations intermittently to obtain the wave form with the sampling frequency of 1,024 Hz.…”
Section: Analysis Of Van Allen Probe and Arase Observationsmentioning
confidence: 99%
“…In this study, we report Pc4 ULF waves and proton flux oscillations observed by the Arase satellite (Miyoshi et al, ) and ground magnetometers on 15 April 2017. We estimate the radial gradient of the proton phase space density 1.61emfH+∂L,3.0235ptwhere3.0235ptfH+ is the proton phase space density 1.61em from the radial motion of Arase to examine the instability condition.…”
Section: Introductionmentioning
confidence: 74%
“…The Arase satellite, whose main objective is exploration of the outer radiation belt, was launched on 20 December 2016 into an elliptical orbit with the apogee of ∼6 R E and the perigee altitude of 300 km (Miyoshi et al, ). The satellite is spin stabilized ( τ spin ∼8 s, where τ spin is the spin period) and equipped with comprehensive sensors for fields and particles.…”
Section: Instrumentationmentioning
confidence: 99%
“…The hypothesis of pulsating aurora needed confirmation by simultaneous observations with a high‐speed auroral camera, but permanent auroral observation in the region was routinely made at a rate of one frame in a few seconds at best, which is not enough to resolve the 2‐Hz variations. Only at the end of 2016 suitable high‐speed cameras were installed in Northern Europe in association with the Exploration of energization and Radiation in Geospace project (Miyoshi et al, ). In the present paper we study in detail a unique case from 6 November 2016 when the MR detected NED auroral echoes from the region where successful auroral observations were made with the high‐speed camera.…”
Section: Introductionmentioning
confidence: 99%